Design of Forward Adaptive Uniform Quantizer for Discrete Input Samples for Laplacian Source - Savić, M.; Perić, Z.; Dinčić, M. (Elektronika ir Elektrotechnika, 2010)
In this paper, the problem of construction of the fixed and the forward adaptive uniform quantizer for input samples with discrete amplitude is analyzed, for Laplacian source. This quantizer is very common in practice; therefore its analysis is very significant. It is shown that design and performances of the quantiazer for discrete input samples are very different, compared to quantizer for continual input samples.